A Case Series of Foreign Body Aspiration - Jagram Verma; Sonith Peter George; Ritu Verma Ahirwar; Anshul Sharma (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
Introduction: Foreign body (FB) aspiration is a common problem in children, requiring early diagnosis and prompt treatment to avoid potentially life-threatening complications. FB aspiration still remains an important cause of childhood deaths, especially in pre-school children. Early recognition with a high index of suspicion remains a critical factor in the treatment of FB inhalation in children. Methodology: We are presenting a case series of six cases of foreign body in the airway who presented to the emergency department of M.G.M Medical College and M.Y. Hospital, Indore with complaints of sudden onset cough or difficulty in breathing. Discussion: Foreign Body aspiration is a common but potentially life-threatening emergency in the pediatric age group. This case series proves to show the necessity of timely diagnosis and appropriate management by bronchoscopic removal in cases of Foreign body aspiration. Conclusion: Foreign body aspiration continues to be a growing challenge for ENT surgeons since it is critical to diagnose and manage such patients as quickly as possible with no time to waste. Rigid bronchoscopy continues to remain the Gold standard treatment modality with Hopkins Rod Telescope and Optical Forceps being the new advances in this field.